Discrete-Event Simulation of Quantum Walks - Willsch, Madita; Willsch, Dennis; Michielsen, Kristel; De Raedt, Hans (Frontiers in Physics, 2020)
We use discrete-event simulation on a digital computer to study two different models of experimentally realizable quantum walks. The simulation models comply with Einstein locality, are as “realistic” as the one of the simple random walk in that the particles follow well-defined trajectories, are void of concepts, such as particle-wave duality and wave-function collapse, and reproduce the quantum-theoretical results by means of a cause-and-effect, event-by-event process. Our simulation model for the quantum walk experiment presented in Robens et al. [1] reproduces the result of that experiment. Therefore, the claim that the result of the experiment “rigorously excludes (i.e., falsifies) any explanation of quantum transport based on classical, well-defined trajectories” needs to be revised.